Odpowiedzi

Najlepsza Odpowiedź!
2010-01-10T15:55:09+01:00
2*(x+7)=3*(2x-5)

2x+14 = 6x -15
2x - 6x = -15 - 14
-4x = -29 / : ( -4)
x = 7,25

spr:
2 * ( 7,25 +7 ) = 3 * (2 * 7,25 -5 )
14,5 + 14 = 43,5 - 15
28,5 = 28,5
L = P


3*(x-5)+7=x+1

3x - 15 + 7 = x + 1
3x - 8 = x + 1
3x - x = 1 + 8
2x = 9 / : 2
x = 4,5

spr:
3 * ( 4,5 - 5 ) + 7 = 4,5 + 1
13,5 - 15 + 7 = 5,5
13,5 - 8 = 5,5
5,5 = 5,5
L = P

POZDRAWIAM :)
1 5 1
2010-01-10T15:55:25+01:00
2*(x+7)=3*(2x-5)
2x+14=6x-15
29=4x
x=7,25

spr
L=2*(7,25+7)=2*14,25=28,5
P=3*(2*7,25-5)=3* (14,5-5)=3* 9,5=28,5

3*(x-5)+7=x+1
3x-15+7=x+1
2x-8=1
2x=9
x=4,5

spr
L=3*(4,5-5)+7= 3*(-0,5)+7= -1,5+7= 5,5
P=4,5+1=5,5
1 5 1
2010-01-10T16:10:02+01:00
3(x-5)+7=x+1 L=3(x-5)+7=3(4,5-5)+7=13,5-15+7=5,5
3x-15+7=x+1 P=x+1=4,5+1=5,5
3x-x=1+15-7 L=P
2x=9/2
x=4,5



2(x+7)=3(2x-5) L=2(x+7)=2(7,25+7)=14,5+14=28,5
2x+14=6x-15 P=3(2x-5)=3(2*7,25-5=3(14,5-5)=43,5-15=28,5
2x-6x=-15+14
-4x=-29/-4 L=P
x=7,25